Current Communicative Language Teaching Aproaches - Kuteish, Irena (Beirut Ligue des Professeurs de l'U.L, 2005)
The purpose of this paper is to indicate the nature of general and specific problematic areas of the communicative approach and to trace the origins and reasons that led to their emergence without intending to provide an exhaustive account of problems and tensions in such a survey. The paper discussed the fact that language teaching has been witnessing two dramatically opposing tendencies: the tendency of integration in order to establish a standardized way of teaching in the form of a widely recognized and accepted approach, on the one hand; and the tendency of diversity and fragmentation that was clearly explicated by the opponents of the post-method era. Besides, the paper concluded that the language teaching profession is in need of refining, reshaping and judicious integration of current communicative approaches into a homogeneous enterprise within a broader framework of a developmental educational enterprise whose mission is believed to be transmission, relocation and sustention of culture and humanity.
: Article
Keywords: English Language Education Teaching Methods; L enseignement de la Langue Anglaise Méthodes d enseignement